1998
DOI: 10.1002/(sici)1521-3773(19980817)37:15<1986::aid-anie1986>3.0.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Carbonyl Compounds with Chiral Oxazaborolidine Catalysts: A New Paradigm for Enantioselective Catalysis and a Powerful New Synthetic Method

Abstract: High enantioselectivity can be achieved when chiral oxazaborolidines are used as catalysts in the reduction of ketones by borane. In the transition state on the way to the complex chiral compounds, the two reactants are activated and held in close proximity by the catalyst, as shown below.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
186
0
4

Year Published

1998
1998
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 1,260 publications
(191 citation statements)
references
References 52 publications
1
186
0
4
Order By: Relevance
“…Synthesis of enantiopure amino alcohols is of great importance in synthetic organic chemistry since they are a well established source of ligands for asymmetric synthesis (Blaser 1992;Ager et al 1996;Lait et al 2007) including enantioselective borane reduction of prochiral ketones (Corey et al 1987;Corey and Helal 1998;Deloux and Screbnik 1993;Li et al 1999;Krzemiński and Wojtczak 2005;Krzemiński and Zaidlewicz 2003;Hobuss et al 2008) or enantioselective addition of dialkylzinc (Kitamura et al 1986;Kossenjans and Martens 1998;Garcia Martinez et al 2002;Oliveira and Costa 2004;Szakonyi et al 2006;Binder et al 2009;Scarpi et al 2009;Wu et al 2009). Apart from this property, enantiopure amino alcohols are also important derivatives for the synthesis of various chemical compounds.…”
Section: Introductionmentioning
confidence: 91%
“…Synthesis of enantiopure amino alcohols is of great importance in synthetic organic chemistry since they are a well established source of ligands for asymmetric synthesis (Blaser 1992;Ager et al 1996;Lait et al 2007) including enantioselective borane reduction of prochiral ketones (Corey et al 1987;Corey and Helal 1998;Deloux and Screbnik 1993;Li et al 1999;Krzemiński and Wojtczak 2005;Krzemiński and Zaidlewicz 2003;Hobuss et al 2008) or enantioselective addition of dialkylzinc (Kitamura et al 1986;Kossenjans and Martens 1998;Garcia Martinez et al 2002;Oliveira and Costa 2004;Szakonyi et al 2006;Binder et al 2009;Scarpi et al 2009;Wu et al 2009). Apart from this property, enantiopure amino alcohols are also important derivatives for the synthesis of various chemical compounds.…”
Section: Introductionmentioning
confidence: 91%
“…Stereoselective reduction of prochiral ketones into chiral nonracemic secondary alcohols is a fundamental process in organic synthesis and accordingly many chemical (Noyori & Hashiguchi 1997, Corey & Helal 1998, Cho 2002 and biocatalytic (Nakamura et al 2003, Kroutil et al 2004) processes have been reported. Recently, plants have been considered as suitable biochemical systems for the biotransformation of exogenous substrates (Ishihara et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent oxidation and iodide-catalyzed (double bond) isomerization then gave enones 63 and 64, which served as the scaffolds for the stereodiversifying point to all 15-F 2 -IsoPs. Corey's CBS reduction (Corey and Helal, 1998) or classical resolution was applied to install the desired -side chain in enantiomerically pure 65/66 and 69a,b/70a,b. Re-oxidation of 65 and 66, followed by a second application of either antipode of 2-methyl-CBS-oxazoborolidine, allowed access to both C-15 epimers for each series; subsequent hydroboration then afforded enantiomerically pure 67a,b and 68a,b.…”
Section: Divergent Synthesis Of 1ab and 2abmentioning
confidence: 99%